Reactive thrombocytosis in children - Özcan, Celal; Şaylı, Tülin Revide; Koşan-Çulha, Vildan (The Turkish Journal of Pediatrics, 2013)
The aim of this study was to evaluate the causes of thrombocytosis, which was defined as a platelet count greater than 500 x 10(9)/L, and to compare the groups with mild and severe thrombocytosis. A total of 484 patients were evaluated for the etiology of thrombocytosis. Patients with a platelet count between 500-800 x 10(9)/L were considered to have mild thrombocytosis, while those with a count of ≥800 x 10(9)/L were considered as having severe thrombocytosis. Of 484 patients included, 63% had thrombocytosis due to an infectious disease, 11.4% had a chronic inflammatory condition, 8.5% had anemia, and 5.2% had tissue injury. The frequency of chronic inflammation was higher in the severe thrombocytosis group compared to the mild thrombocytosis group (p=0.006). In conclusion, severe infections and chronic inflammatory conditions should be considered in the differential diagnosis of a patient with severe thrombocytosis.